Storage Limitation Statements: Temperature--Herbicides - Frederick M. Fishel (EDIS)
PI-123, a 9-page guide by Frederick M. Fishel, provides general temperature effects on storage properties of agricultural herbicides. A 7-page table is included which lists many of the common agricultural herbicides registered for use in Florida, with storage limitations statements. Published by the UF Agronomy Department, June 2006.